2007
DOI: 10.1590/s0066-782x2007000300013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de hipertensão arterial sistêmica na cidade de Formiga, MG

Abstract: SummaryObjectives: To estimate hypertension prevalence and identify associated socioeconomic, demographic, and anthropometric variables.Methods: urban area of Formiga, Minas Gerais state, and registered with the Family Health Program (Programa Saúde da Família -PSF), which covers 94% of the population. Two hundred and eighty-five subjects (131 men and 154 women) were was used to collect socioeconomic and demographic data, as well as information on alcohol consumption, smoking, and physical activity level. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0
11

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
4
6
0
11
Order By: Relevance
“…The prevalence of hypertension observed in the sample (diagnosed: 43%, and self-reported: 42%) was high and consistent with the values found in other studies previously carried out in the country, considering the methodological differences, the growing number of patients with the disease and its higher prevalence in Sao Paulo 2,7,10,12,14,[17][18][19] . The validity of self-reported hypertension and its association with overweight was similar to that of other national and international studies, although methodological differences between the validation studies on self-reported hypertension can make it difficult to compare the results 8,11,13 .…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of hypertension observed in the sample (diagnosed: 43%, and self-reported: 42%) was high and consistent with the values found in other studies previously carried out in the country, considering the methodological differences, the growing number of patients with the disease and its higher prevalence in Sao Paulo 2,7,10,12,14,[17][18][19] . The validity of self-reported hypertension and its association with overweight was similar to that of other national and international studies, although methodological differences between the validation studies on self-reported hypertension can make it difficult to compare the results 8,11,13 .…”
Section: Discussionsupporting
confidence: 88%
“…In Brazil, there are a few population based studies referring to the prevalence of AH. Most of them are focused on cities or regions [8][9][10][11][12][13] . In general, studies present methodological differences (sample, population groups, age group, and diagnostic criteria) that make comparability more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In general, studies present methodological differences (sample, population groups, age group, and diagnostic criteria) that make comparability more difficult. However, prevalence ranges from 15 to 40% in the urban adult Brazilian population [8][9][10][11][12][13][14] . Due to the methodological difficulties to measure blood pressure in population studies, analyses that employ self-reported data have been used as a proxy measure, even if it is not gold-standard for the evaluation of blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…A prevalência de hipertensão arterial nos Estados Unidos tem se mantido constante nos últimos dez anos, com uma taxa de cerca de 30% 2 . No Brasil, estudos demonstram uma prevalência de hipertensão arterial variando de 25,2% a 40,1%, com média acima de 30% [3][4][5][6][7][8] , e esse número aumenta consideravelmente na população acima dos 60 anos de idade 2,9 . Segundo os últimos dados do IDB (Indicadores e Dados Básicos) Brasil, a média da prevalência de hipertensão arterial nas capitais do Brasil em adultos com 18 anos ou mais de idade, no ano de 2012, era de 24,3%.…”
Section: Introductionunclassified